Double-objective economic statistical design of the VP T-2 control chart: Wald's identity approach - Faraz, Alireza; Heuchenne, Cedric; Saniga, Erwin; Costa, Antonio F. B. [UNESP] (Taylor & Francis Ltd, 2014)
Research has shown that applying the T-2 control chart by using a variable parameters (VP) scheme yields rapid detection of out-of-control states. In this paper, the problem of economic statistical design of the VP T-2 control chart is considered as a double-objective minimization problem with the statistical objective being the adjusted average time to signal and the economic objective being expected cost per hour. We then find the Pareto-optimal designs in which the two objectives are met simultaneously by using a multi-objective genetic algorithm. Through an illustrative example, we show that relatively large benefits can be achieved by applying the VP scheme when compared with usual schemes, and in addition, the multi-objective approach provides the user with designs that are flexible and adaptive.
Keywords: Hotelling's T-2 control chart; adjusted average time to signal; variable parameters; economic statistical design; Wald's identity; multi-objective genetic algorithm